MÜZE ve TARİHİ MEKÂNLARDA DEĞER ve BECERİ KAZANDIRMAYA YÖNELİK SOSYAL BİLGİLER ÖĞRETMEN ADAYLARININ GÖRÜŞLERİ. - ÖNER, Galip; KÖSE, Tuba ÇENGELCİ (Turkish History Education Journal (TUHED))
One of the elements that come to mind when it comes to out-of-school education environments are museums and historical places. When the literature is examined, it is seen that these places allow students to gain many achievements, in particular by concretizing the abstract issues and providing permanently marked learning in students. In other words, it states that students get permanent information in museums and historical places. Considering that access to information is relatively easy in formal or informal environments, it is thought to be more important to provide value and skill to students. However, in the literature, studies on the use of museums and historical sites in the teaching of value and skills in social studies courses are quite limited. In this context, the aim of the research is to reveal the opinions and experiences of the social studies teacher candidates on providing value and skills to students in museums and historical places. In the research, basic qualitative research, which is one of the qualitative research methods is used. The data from the research are obtained from preservice teachers, who study at Erciyes University Social Sciences Teaching Program [at the first stage from 44 (feedback form), at the second stage from 27 (feedback form), at the third stage from 17 preservice teachers (interview)]. Qualitative data were analyzed using descriptive analysis technique with the help of Nvivo 11 package program. As a result of the research it was determined that preservice teachers think that values such as patriotism, solidarity, responsibility, respect, cooperativeness, freedom, independency, assiduity, being scientific, aesthetic, sensitivity, tolerance, honesty, love, peace and giving importance to unity of family; skills such as empathy, space detection, observation, social participation, time and chronology detection, communication, creative thinking and correct and good use of Turkish can be provided in the social sciences course in museum.